Association of Treatment Facility Characteristics With Overall Survival After Mohs Micrographic Surgery for T1a-T2a Invasive Melanoma - Cheraghlou, Shayan (JAMA Dermatol, 2021)
IMPORTANCE: Early-stage melanoma, among the most common cancers in the US, is typically treated with wide local excision. However, recent advances in immunohistochemistry have led to an increasing number of these cases being excised via Mohs micrographic surgery (MMS). Although studies of resections for other cancers have reported that facility-level factors are associated with patient outcomes, it is not yet established how these factors may affect outcomes for patients treated with Mohs micrographic surgery. OBJECTIVE: To evaluate the association of treatment center academic affiliation and case volume with long-term patient survival after MMS for T1a-T2a invasive melanoma. DESIGN, SETTING, AND PARTICIPANTS: In a retrospective cohort study, 4062 adults with nonmetastatic, T1a-T2a melanoma diagnosed from 2004 to 2014 and treated with MMS in the National Cancer Database (NCDB) were identified. The NCDB includes all reportable cases from Commission on Cancer–accredited facilities and is estimated to capture approximately 50% of all incident melanomas in the US. Multivariable survival analyses were conducted using Cox proportional hazards models. Data analysis was conducted from February 27 to August 18, 2020. EXPOSURES: Treatment facility characteristics. MAIN OUTCOMES AND MEASURES: Overall survival. RESULTS: The study population included 4062 patients (2213 [54.5%] men; median [SD] age, 60 [16.3] years) treated at 462 centers. Sixty-two centers were top decile–volume facilities (TDVFs), which treated 1757 patients (61.9%). Most TDVFs were academic institutions (37 of 62 [59.7%]). On multivariable analysis, treatment at an academic center was associated with a nearly 30% reduction in hazard of death (hazard ratio, 0.730; 95% CI, 0.596-0.895). In a separate analysis, treatment at TDVFs was also associated with improved survival (hazard ratio, 0.795; 95% CI, 0.648-0.977). CONCLUSIONS AND RELEVANCE: In this cohort study, treatment of patients with T1a-T2a invasive melanoma excised with MMS at academic and top decile–volume (≥8 cases per year) facilities was associated with improved long-term survival compared with those excised by MMS at nonacademic and low-volume facilities. Identification and protocolization of the practices of these facilities may help to reduce survival differences between centers.